Components of Competitiveness of Small and Medium Businesses Case of Covid 19 Crisis - Kanwivat, Somrerk (Journal of Public Administration Chiang Rai Rajabhat University, 2023)
The objectives of this article are: To study the components of competitiveness of SMEs in the case of the Covid-19 crisis by the components of competitiveness of small and medium businesses Case of the COVID-19 crisis in the study of knowledge, concepts, and theories involved From documents and research, there are two components: Element 1, low cost vs. Element 2, differentiation. There are three sub-components of differentiation, namely, Element 2.1 Differentiation in marketing mix strategy, Component 2.2 Quality Differentiation and Component 2.3 Marketing Differentiation.